Patterns of content and sharing among social media users in Malaysia - Mohd Radzi, Siti Ramizah Khairunnisa; Bolong, Jusang; Osman, Mohd Nizam; Adzharuddin, Nor Azura (Human Resource Management Academic Research Society, 2022)
There is a possibility for a user to unintentionally over or misuse the technology when sharing or receiving content with others. As a result, individuals will confront distrust issues, emotional disturbance, and information confusion stemming from user actions. This study aims to determine the patterns of content and sharing in social media. By using online survey research, a total of 408 users aged 20 years and above were selected through convenience sampling and required to answer a set of questionnaires through Google forms. The result shows that the majority of the users prefer to share rather than commenting and resharing the information on social media. They were interested in sharing topics related to health and current issues, or comments and re-share topics on humor and jokes. In conclusion, intentionally sharing information would stimulate a content to be viral on social media.